Efektivitas Program Pelayanan Kolaborasi Administrasi Kependudukan Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Gowa - Anis, Irawani; Usman, Jaelan; Arfah, Sitti Rahmawati (Universitas Muhammadiyah Makassar, 2021)
This study purposed was to determine the effectiveness of the Population Administration Collaboration Service Program in the Department of Population and Civil Registration of Gowa. This study used qualitative descriptive research type. Data collection techniques using the method of observation, interviews, and documentation. Data analysis techniques using data reduction steps, data presentation, and conclusions. The results showed from the indicators of measuring the effectiveness of understanding of the program was quite good, seen from each party and the community had understood their duties and responsibilities in implementing the Pak Adnan program. accuracy of targeting, had achieved through collaboration carried out by each party in the Pak Adnan program. Punctuality could not be said to be effective because there were still various obstacles so that the time needed to complete the birth certificate was not as determined. The achievement of the objectives could not be said to have been achieved because there were still parties or people who had not felt the ease in implementing the Pak Adnan program, and real changes could not be said to be effective because they were only able to provide real changes to the collaborating parties, Keywords: Effectiveness, Service, Administration.